NON-CLOTTING HAEMOLYMPH OF WSSV-INFECTED SHRIMP: IS IT A FACTOR IN INFECTION PROCESSES? - Coco Kokarkin Soetrisno (Indonesian Aquaculture Journal, 2009)
White spot syndrome virus is recognized as the most prominent pathogen of penaeid shrimp and has been affecting this shrimp farming industry around the world. The virus may reduce the shrimp’s immune response and alter enzymatic and biochemical composition of tissues. Similar to other environmental stressed or other pathogeninfected shrimp, in late stages of WSSV infection, shrimp will fail to clot the haemolymph, so any minor injury will lead to increased haemolyph loss. A series of experiments to determine the effect of non-clotting haemolymph on WSSV infection were carried out in controlled facilities in Indonesia. The preliminary test showed that normal clotting time was 13.3 seconds while WSSV-injected shrimp mostly failed to clot their haemolymph 16 hours post infection (hpi). Some other clinical signs such as abnormal swimming, red discoloration, white spots and mortality were consistent with those observed by previous studies. Three shrimp species: banana shrimp (P. merguiensis) 9 g , white leg shrimp (P. vannamei) 7 g and the tiger shrimp (P. monodon) 16.5 g were water-borne-challenged with non-clotting, WSSV-infected haemolymph (NCH) from tiger shrimp donor in duplicate tanks each with 12 shrimp. The control were tiger shrimps fed with WSSV-infected tissue at the rate of 40% of bodyweight (BW) and other tiger shrimps were used as negative controls fed with commercial feed only.The study revealed that NCH dosages of 1.46%; 2.03%; and 2.06% (v/v) for eachspecies were sufficient to infect and kill all shrimps in less than two days comparedto eight days for the shrimps fed on infected tissue. The WSSV in non-clottedhaemolymph eventuallyattaches into the living tissues of healthy shrimp. This modeof infection is likely more difficult to control by the ordinary fine mesh screeningmethod.